TiO2 Nanowire Arrays in situ Grown on Ti Foil Exhibiting Superior Uranyl-Adsorption Properties - Chen, Chun; Zhong, Yi; Liu, Xuxu; Li, Xijian; Chu, Jian; Yu, Libing; Yang, Zhenliang; Li, Bingqing; Tang, Wei; Xiong, Zhonghua; Gao, Rui (Frontiers in Materials, 2021)
TiO2 nanowire arrays in-situ grown on Ti foil (TiO2/Ti) were prepared to remove uranium (VI) from aqueous solution. As the Ti foil serves as a carrier for TiO2, the TiO2/Ti adsorbent can be easily separated from aqueous solutions by tweezers after adsorption. The adsorbent was characterized by X-ray diffraction and scanning electron microscopy. The effect factors in adsorption process were fully investigated, including solution pH, contact time, temperature and uranium (VI) concentration. The maximum adsorption capacity of uranium (VI) was calculated to be 354.5 mg g-1 at pH 5.0 and T=323 K by the Langmuir model. Thermodynamic parameters showed that the adsorption of uranium (VI) on TiO2/Ti is an endothermic and spontaneous process. The reusability studies demonstrated that the adsorption capacity of TiO2/Ti hardly decreased even after a three-cycle adsorption in uranium (VI) solutions. Therefore, the prepared TiO2/Ti adsorbent could be potentially used to remove uranium (VI) from water in future practical applications.